Companion Publication of the 2021 Conference on Computer Supported Cooperative Work and Social Computing 2021
DOI: 10.1145/3462204.3481729
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and Mitigating Biases in Crowdsourced Data

Abstract: It is common practice for machine learning systems to rely on crowdsourced label data for training and evaluation. It is also wellknown that biases present in the label data can induce biases in the trained models. Biases may be introduced by the mechanisms used for deciding what data should/could be labelled or by the mechanisms employed to obtain the labels. Various approaches have been proposed to detect and correct biases once the label dataset has been constructed. However, proactively reducing biases dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Several techniques have been proposed to handle such bias post‐creation, including improving linguistic diversity of samples [YZFBC * 20, LML * 19, SYH20] and augmenting data with adversarial samples intended to fool the model [WRF * 19,KBN * 21,TYLB * ]. Similarly, there is evidence that natural language instructions provided by dataset creators during crowdsourcing influences crowdworkers to follow specific patterns during sample creation [GGB19,PMGB22, HSG * 21]. These patterns, termed as ‘instruction bias,‘ propagate to the dataset and are subsequently over‐represented in the collected data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques have been proposed to handle such bias post‐creation, including improving linguistic diversity of samples [YZFBC * 20, LML * 19, SYH20] and augmenting data with adversarial samples intended to fool the model [WRF * 19,KBN * 21,TYLB * ]. Similarly, there is evidence that natural language instructions provided by dataset creators during crowdsourcing influences crowdworkers to follow specific patterns during sample creation [GGB19,PMGB22, HSG * 21]. These patterns, termed as ‘instruction bias,‘ propagate to the dataset and are subsequently over‐represented in the collected data.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, prior work in crowdsourcing has shown that task instructions provided by dataset creators often influence crowd‐workers to follow specific patterns during instance creation. This leads to collection of biased data, which inflates model performance [GGB19, PMGB22, HSG * 21]. This is particularly critical in high‐risk domains such as healthcare [MA21a], where incorrect answers to a task can prove fatal.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were evident from work by Hube, Fetahu, and Gadiraju (2019), who found that crowd workers with strong opinions produce biased annotations, even evident among experienced workers. Furthermore, demographics, location, worker context, and work en-vironment have been found to impact annotation quality in both subjective and objective tasks (Hettiachchi et al 2021).…”
Section: Subjective Annotation Tasksmentioning
confidence: 99%
“…Crowdsourcing has been a widely adapted approach to create large scale datasets such as SQUAD 1.1 (Rajpurkar et al, 2016(Rajpurkar et al, , 2018, DROP (Dua et al, 2019), QUOREF and many more (Najafabadi et al, 2015;Callison-Burch and Dredze, 2010;Lasecki et al, 2014;Zheng et al, 2018;Chang et al, 2017). Many past works investigate different types of bias in crowdsourcing datasets such as cognitive bias (Eickhoff, 2018), annotator bias (Gururangan et al, 2018;Geva et al, 2019), sampling bias (Hu et al, 2020), demographic bias (Rahmani and Yang, 2021) and others (Hettiachchi et al, 2021). Many works on bias in NLU benchmarks focus on biases resulting from the crowdsourcing annotations, and how annotator-specific patterns create biases in data (Geva et al, 2019).…”
Section: A Biases In Nlu Benchmarksmentioning
confidence: 99%
“…Despite the vast success of this method, past studies have shown that data collected through crowdsourcing often exhibit various biases that lead to overestimation of model performance (Schwartz et al, 2017;Gururangan et al, 2018;Poliak et al, 2018;Tsuchiya, 2018;Mishra et al, 2020a;Mishra and Arunkumar, 2021;Hettiachchi et al, 2021). Such biases are often attributed to annotator-related biases, such as writing style and background knowledge (Gururangan et al, 2018;Geva et al, 2019) (see more discussion on related work in §A).…”
Section: Introductionmentioning
confidence: 99%